2008
DOI: 10.1097/tp.0b013e31816a342a
|View full text |Cite
|
Sign up to set email alerts
|

Viral Persistence After Liver Transplantation for Hepatitis B Virus: A Cross-Sectional Study

Abstract: Our observations imply that the selection of resistant virus may be essential, but is not sufficient to cause overt failure of prophylaxis with development of clinical disease. It seems likely that the patients' immune response contributes, at least partially, to the long-term control of infection in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 43 publications
0
31
0
Order By: Relevance
“…Post-LT a : Viral suppression is the goal for all patients before liver transplantation using Entecavir or There was no significant difference in the proportion of HBsAg positivity between the LAM, ETV, or combination therapy groups (20,17, and 21 %). These studies highlight several important issues to consider regarding HBV prophylaxis using HBIG-free regimens.…”
Section: Time Of Lt Amentioning
confidence: 96%
“…Post-LT a : Viral suppression is the goal for all patients before liver transplantation using Entecavir or There was no significant difference in the proportion of HBsAg positivity between the LAM, ETV, or combination therapy groups (20,17, and 21 %). These studies highlight several important issues to consider regarding HBV prophylaxis using HBIG-free regimens.…”
Section: Time Of Lt Amentioning
confidence: 96%
“…HBsAb [100 IU/l without HBIg administration for more than 3 months was judged to indicate success of this vaccine protocol according to the previous reports for HBV prophylaxis [11,26,27] and vaccine effect [28,29]. If this level could be attained, lamivudine treatment could be stopped.…”
Section: Study Protocolmentioning
confidence: 99%
“…Although the sample size of the patients-studied was low in compare with Lam-receiving patients, the reported recurrence after prophylaxis with ADV was 0% [44,87,99] . Among new NAs, entecavir, telbivudine, tenofovir and emtricitabine have been used with 0% recurrence rate (Table 2) [22, 46,56,93,95,[100][101][102][103][104][105] .…”
Section: Hbig+na Prophylaxismentioning
confidence: 99%
“…Further, comparison of trails that used a combination of antivirals compared with a combination of HBIg plus either NA alone showed that both regimens provides equivalent protection against recurrent HBV infection after LTx with fewer side effects and lower cost [32,88] . Furthermore, treatment with adefovir plus lamivudine before LTx and the addition of HBIg after LTx has shown to prevent graft reinfection [7,87,94,99] .…”
Section: Conflict Of Interestsmentioning
confidence: 99%
See 1 more Smart Citation